Genetic contribution and functional impairment of inflammasome in sickle cell disease. (January 2022) - de Freitas Dutra, Valéria; Leal, Vinícius Nunes Cordeiro; Fernandes, Fernanda Pereira; Souza, Cláudia Regina Lustosa; Figueiredo, Maria Stella; Pontillo, Alessandra
Highlights: Inflammasome could represent an important contributor in SCD pathogenesis. Monocytes and PBMC from SCD exhibited different NLRP3 inflammasome activation rate. Gain-of-function in NLRP1 and IL1B genes was associated with mild SCD presentation. Abstract: Background: Sickle cell disease (SCD), one of the most common single-gene disorders, is caused by mutations in the hemoglobin ß-chain gene. Clinical presentation is heterogeneous, and inflammation is a common condition. Thereby, we hypothesized that inflammasome and related cytokine IL-1ß could represent significant SCD pathogenesis contributors. Material and methods: 161 SCD (SS/Sβ) patients were enrolled for the study. Seven single nucleotide polymorphisms (SNPs) in 5 inflammasome genes ( NLRP1, NLRP3, NLRC4, CARD8, IL1B ) were selected based on minor allele frequency. Total peripheral blood mononuclear cells (PBMC) and monocytes were isolated from 10 out of 161 SCD patients (HbSS) and 10 healthy donors (control group, Ctrl) for inflammasome analysis. Results: SCD patients presented a functional impairment of inflammasome, with monocytes and peripheral blood mononuclear cells (PBMC) exhibiting a different NLRP3 inflammasome activation rate. Gain-of-function variants in NLRP1 and IL1B genes resulted associated with a mild SCD clinical presentation. Discussion: Our results can contribute to the understanding of SCD inflammation. SCD patients showed possible exhaustion of monocytes due to chronic inflammation, moreover others cells in PBMC can contribute to the NLRP3 inflammasome activation. NLRP1 gain-of-function was associated with mild clinical presentation, suggesting that other inflammasome receptors can be involved in SCD. This is the first study reporting a significant contribution of inflammasome SNPs in SCD.